The Relationship between Creative Thinking in Mathematics and Mathematical Modeling among University Students - Batoul M. Al-Eisa; Mamoun M. Al-Shunnaq; Eid M. Kana'an (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
The study aims to reveal the relationship between creative thinking in mathematics and mathematical modeling among university students. The sample consisted of (120) mathematics and engineering students from Yarmouk University and Jordan Science and Technology University, during the summer semester of 2018/2019 academic year, who were selected by cluster sample method. Creative thinking in mathematics and mathematical modeling tests were used. The results showed that the creative thinking in mathematics and mathematical modeling levels among students was moderate. The results also showed a significant differences in mathematical modeling due to the specialization variable in favor of engineering students, while showed no differences due to gender; it's also showed no differences in creative thinking in mathematics due to gender and specialization variables. Moreover, the results showed a strong positive correlations between creative thinking in mathematics and mathematical modeling. According to these findings, the study recommended that students should be given the opportunity to practice creative thinking and mathematical modeling and skills through enriching school curricula and university courses with activities and tasks rich in life situations that require mathematical modeling.